CaMKIIδC Drives Early Adaptive Ca2+ Change and Late Eccentric Cardiac Hypertrophy. Issue 9 (9th October 2020) - Ljubojevic-Holzer, Senka; Herren, Anthony W.; Djalinac, Natasa; Voglhuber, Julia; Morotti, Stefano; Holzer, Michael; Wood, Brent M.; Abdellatif, Mahmoud; Matzer, Ingrid; Sacherer, Michael; Radulovic, Snjezana; Wallner, Markus; et al.
Abstract : Rationale: CaMKII (Ca 2+ -Calmodulin dependent protein kinase) δC activation is implicated in pathological progression of heart failure (HF) and CaMKIIδC transgenic mice rapidly develop HF and arrhythmias. However, little is known about early spatio-temporal Ca 2+ handling and CaMKII activation in hypertrophy and HF. Objective: To measure time- and location-dependent activation of CaMKIIδC signaling in adult ventricular cardiomyocytes, during transaortic constriction (TAC) and in CaMKIIδC transgenic mice. Methods and Results: We used human tissue from nonfailing and HF hearts, 4 mouse lines: wild-type, KO (CaMKIIδ-knockout), CaMKIIδC transgenic in wild-type (TG), or KO background, and wild-type mice exposed to TAC. Confocal imaging and biochemistry revealed disproportional CaMKIIδC activation and accumulation in nuclear and perinuclear versus cytosolic regions at 5 days post-TAC. This CaMKIIδ activation caused a compensatory increase in sarcoplasmic reticulum Ca 2+ content, Ca 2+ transient amplitude, and [Ca 2+ ] decline rates, with reduced phospholamban expression, all of which were most prominent near and in the nucleus. These early adaptive effects in TAC were entirely mimicked in young CaMKIIδ TG mice (6–8 weeks) where no overt cardiac dysfunction was present. The (peri)nuclear CaMKII accumulation also correlated with enhanced HDAC4 (histone deacetylase) nuclear export, creating a microdomain for transcriptional regulation. At longer times both TAC and TG mice progressed to overt HF (at 45 days and 11–13 weeks, respectively), during which time the compensatory Ca 2+ transient effects reversed, but further increases in nuclear and time-averaged [Ca 2+ ] and CaMKII activation occurred. CaMKIIδ TG mice lacking δB exhibited more severe HF, eccentric myocyte growth, and nuclear changes. Patient HF samples also showed greatly increased CaMKIIδ expression, especially for CaMKIIδC in nuclear fractions. Conclusions: We conclude that in early TAC perinuclear CaMKIIδC activation promotes adaptive increases in myocyte Ca 2+ transients and nuclear transcriptional responses but that chronic progression of this nuclear Ca 2+ -CaMKIIδC axis contributes to eccentric hypertrophy and HF. Abstract : Supplemental Digital Content is available in the text.